Analysis of Health Knowledge Factors Affecting Interest in Using an Electric Cigarette in Indonesia - Poppy Putri Pratiwi (HM Publisher, 2020)
Smoking is the activity of smoking a rolled tobacco wrapped and then burning and exhaling the smoke back out. Nowadays many smokers switch to using e-cigarettes. Nicotine replacement therapy (NRT) is a method that uses a medium to provide nicotine that is needed by smokers without burning tobacco. Electronic cigarette or e-cigarette is one of the NRT that uses electricity from battery power to provide nicotine in the form of steam. The purpose of this study was to determine the factors of health knowledge on the interest in using electronic cigarettes in Indonesia. This type of research is quantitative analytic research with cross sectional study approach. The subjects of this study were 6180 Indonesian people taken by using the Google form with consecutive sampling techniques. The study was conducted on 1 October until 13 October 2019. Data analysis was performed with the Chi-Square test and Logistic Regression on SPSS applications. The results of this study indicate that the knowledge of Indonesian people who agree to prefer not to have an interest in the use of electric cigarettes